Evaluating the Effectiveness of Digital Advertising Campaigns Based on The User's Behavioral Response An Applied Study of The Syrian User's Response To The Digital Ads of The Syrian Ministries of Health And Information on Corona Virus (Journal of Hama University, 2020)
The research covered the concept of digital advertising, in addition to how to evaluate the effectiveness of digital advertising campaigns. Based on the user's behavioral response according to the AIDA model. The research aimed to evaluate the effectiveness of the digital advertising campaign carried out by the Syrian Ministries of Health and Information on the subject of Corona Virus in digital platforms. Application to the Syrian user. A digital questionnaire was designed in accordance with the AIDA model used in evaluating the campaign effectiveness. It was shared on social networking sites (Facebook, Twitter, Instagram), and the researcher managed to obtain 389 valid digital questionnaires for statistical analysis. The researcher relied on SPSS in a process The analysis. Based on the statistical description and testing of research hypotheses, it can be said that the digital advertising campaign carried out by the Ministries of Health and Information on the subject of Corona Virus was effective. The researcher has suggested a number of recommendations, which are expected in the case of their application; To help improve the effectiveness of future digital advertising campaigns on the subject of Corona Virus, or similar subject.